How social media facilitate public participation in the election of a new government: A critical analysis of Twitter discourses in Zimbabwe during the 2013 elections - Makombe, Leonard (Stellenbosch : Stellenbosch University, 2017)
Thesis (DPhil)--Stellenbosch University, 2017.